A CRITICAL ANALYSIS OF DHATUMALA (METABOLIC WASTE PRODUCT) (AYUSHDHARA, 2020)
Ayurveda imparts a great emphasis upon the maintenance of positive health of a person. According to WHO, health is a complete state of physical, mental, social, spiritual well being and not merely the absence of disease. Sushruthas quotation regarding Swastha is exactly same which was told many decades back. Healthy body is the outcome of healthy food and lifestyle and it is the basis for health and disease. Nutrient rich diet which is consumed in proper time and amount will help the body which contributes it to maintain the homeostasis. Food has to be properly digested for the nourishment and formation of healthy Dhathu. Digestion takes place in Mahakoshta and as a result of this, food is converted into Prasadamsa and Kittamsa. Dhatus are formed in a series from Rasa to Shukra from this Prasada portion. Dhatus after their Dhatuagni paka is divided into Sara and Kitta bhaga, and from this Kitta bhaga dhatu malas are formed. Malas represent a wide variety of substances produced by the body through different Pakas conducted in the body. Removal of metabolites and waste products are the basic physiological functions of body. Mala are the waste products that need to be eliminated from the body periodically. Scope of the experiment: Here in this article the physiological interpretation of Dhatumala and its need to be flushed out on regular basis is explained. Physiological view point of Dhathumala will help to understand what it is and how it is formed in the body in a better way to the present generation.